Influence of students' learning styles on the effectiveness of instructional interventions - Lehmann, T.; Ifenthaler, Dirk (2012)
This research contributes to answer the question whether learning/cognitive styles of students serve as a justified starting point for creating target-group appropriate instruction. The study was realized in a self-regulated problem-based learning environment. Data of 56 participants on their individual learning styles, their acquired problem solution and their increase in declarative knowledge were collected. Results indicate that a consideration of learning styles to design a matching instruction or learning environment does not transfer into higher quality problem solutions or an enhanced increase in declarative knowledge.